William Langland's "Piers Plowman" : The C Version - Langland, William, 1330?-1400? (Book collections on Project MUSE., 1996)
"William Langland's Piers Plowman is one of the major poetic monuments of medieval England and of world literature. Probably composed between 1372 and 1389, the poem survives in three distinct versions. It is known to modern readers largely through the middle of the three, the so-called B-text. Now, George Economou's verse translation of the poet's third version makes available for the first time in modern English the final revision of a work that many have regarded as the greatest Christian poem in our language." "With its formal singularity, epic-scale vision, and enormous richness of content, this allegorical poem of the late fourteenth century has seized the imagination and interest of a growing and appreciative audience in the twentieth. Langland's remarkable powers of invention and his passionate involvement with the spiritual, social, and political crises of his time lay claim to our attention, and demand serious comparison with Dante's Divine Comedy. Economou's translation preserves the intensity of the poet's verse and the narrative energy of his alliterative long line, the immediacy of the original's story of the quest for salvation, and the individuality of its language and wordplay. Book jacket."--Jacket.